IKZF1 genetic variants rs4132601 and rs11978267 and acute lymphoblastic leukemia risk in Tunisian children: a case-control study - Wassim Y., Almawi; Sana, Mahjoub; Vera, Chayeb; Hedia, Zitouni; Rabeb M., Ghali; Haifa, Regaieg; Touhami, Mahjoub (BMC, 2019)
Background Associations between IKZF1 gene variants and Acute Lymphoblastic Leukemia (ALL) was recently reported. We examined whether the common IKZF1 polymorphisms rs4132601 T/G and rs111978267 A/G are associated with ALL among a Tunisian pediatric cohort. Methods This case-control study involved 170 patients with ALL and 150 control subjects. SNP genotyping was performed by TaqMan® SNP Genotyping Assay. Results The minor allele G of IKZF1 gene polymorphism rs4132601 T/G was significantly higher in ALL cases than in control subjects (P = 0.029), with 1.54-fold increased risk of ALL. The association of rs4132601 with ALL was seen under co-dominant (P = 0.009), recessive (P = 0.006), and additive (P = 0.027) genetic models, of which the co-dominant (P = 0.027) and recessive (P = 0.027) association remained significant after adjusting for covariates, and False Discovery Rate correction. In contrast, no association was noted for rs111978267 variant. Two-locus (rs4132601-rs11978267) IKZF1 haplotype analysis demonstrated association of GA (P = 0.053), with increased ALL risk [OR (95% CI) = 1.58 (1.00–2.51)], which remained significant after controlling for key covariates [aP = 0.046; aOR (95% CI) = 1.61 (1.01–2.57)]. Conclusion We demonstrated the association of IKZF1 polymorphism rs4132601 T/G with increased risk of ALL among Tunisian pediatric cohort, with altered phenotypic changes among ALL patients.